UPAYA MENINGKATKAN HASIL BELAJAR MATEMATIKA MELALUI MODEL PEMBELAJARAN KOOPERATIF TIPE STUDENT TEAMS ACHIEVEMENT DIVISION (STAD) SISWA KELAS VIII.7 SMP NEGERI 1 TEMBILAHAN HULU - Efriyani '; Putri Yuanita; Jalinus ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: This research aimed to improve learning process and mathematics learning outcomes students of class VIII.7 SMP Negeri 1 Tembilahan Hulu in the first semester academic years 2014/2015 with applied of Cooperative Learning Type Student Teams Achievement Division (STAD). The research are two cycles, each cycle has four stages, which are planning, implementation, observation, and reflection. At the end of each cycle, daily tests are carried out. Data collected through observation and tests in the form of daily tests. Observation is used to collect teacher and student activities during learning process, test is used to collect mathematic outcomes and will given in form daily test. The results show the activity of teachers and students in learning has been in line with the lesson plan. Most of the students have participated actively in the learning process that has been exercised, such as step-by-step learning, presenting student worksheets or question papers, responding a fellow classmate’s presentation, and giving learning conclusions. Results of this research indicate that the application of Cooperative Learning Type Student Teams Achievement Division (STAD) can improve learning process and improve the mathematics learning outcomes math class VIII.7 SMP Negeri 1 Tembilahan Hulu in the first semester academic years 2014/2015.Keywords: Learning outcome, Cooperative learning, Student Teams Achievement Division.